2004
DOI: 10.4049/jimmunol.173.9.5679
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Infection and Antigen Display Have Minimal Influence on the Kinetics of the CD4+ T Cell Response to Listeria monocytogenes Infection

Abstract: The T cell response to infection consists of clonal expansion of effector cells, followed by contraction to memory levels. It was previously thought that the duration of infection determines the magnitude and kinetics of the T cell response. However, recent analysis revealed that transition between the expansion and contraction phases of the Ag-specific CD8+ T cell response is not affected by experimental manipulation in the duration of infection or Ag display. We studied whether the duration of infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 67 publications
5
95
5
Order By: Relevance
“…We have now shown that activated IFN-␥ receptor KO CD4 ϩ T cells did not undergo increased apoptosis even when transferred into WT mice, where the BCG growth is under immunological control. In a different study, the duration of infection and Ag display during Listeria infection had a minimal effect on the expansion and contraction of CD4 ϩ T cells (43). Similarly, during infection with attenuated Listeria, the Agspecific CD4…”
Section: Discussionmentioning
confidence: 99%
“…We have now shown that activated IFN-␥ receptor KO CD4 ϩ T cells did not undergo increased apoptosis even when transferred into WT mice, where the BCG growth is under immunological control. In a different study, the duration of infection and Ag display during Listeria infection had a minimal effect on the expansion and contraction of CD4 ϩ T cells (43). Similarly, during infection with attenuated Listeria, the Agspecific CD4…”
Section: Discussionmentioning
confidence: 99%
“…As these populations of cells expand during the immune response, they begin to become detectable four to five days post-L. monocytogenes infection. The primary T cell response peaks seven to nine days post-infection [65] and the extent of this proliferation and differentiation is independent of antigen [66][67][68]. The population of antigen-specific T cells then contracts to a smaller population of stable memory T cells.…”
Section: Cd4 and Cd8 T Cell Responsesmentioning
confidence: 99%
“…In apparent contrast to CD8 T cells, naive CD4 T cells are believed to require longer periods of stimulation to initiate proliferation (5-7) and differentiation into effector cells (8,9). Additionally, in vivo studies indicate that shortening the length of Listeria monocytogenes infection by antibiotic treatment can affect CD4 T cell activation and development of memory T cells, but this effect is dependent on infectious dose, suggesting that overall antigen levels may play a role (10,11). Thus, divergent mechanisms seem to regulate the differentiation of CD4 and CD8 T cells.…”
mentioning
confidence: 99%